Acid-Sensing Ion Channels: Expression and Function in Resident and Infiltrating Immune Cells in the Central Nervous System - Foster, Victoria S.; Rash, Lachlan D.; King, Glenn F.; Rank, Michelle M. (Frontiers in Cellular Neuroscience, 2021)
Peripheral and central immune cells are critical for fighting disease, but they can also play a pivotal role in the onset and/or progression of a variety of neurological conditions that affect the central nervous system (CNS). Tissue acidosis is often present in CNS pathologies such as multiple sclerosis, epileptic seizures, and depression, and local pH is also reduced during periods of ischemia following stroke, traumatic brain injury, and spinal cord injury. These pathological increases in extracellular acidity can activate a class of proton-gated channels known as acid-sensing ion channels (ASICs). ASICs have been primarily studied due to their ubiquitous expression throughout the nervous system, but it is less well recognized that they are also found in various types of immune cells. In this review, we explore what is currently known about the expression of ASICs in both peripheral and CNS-resident immune cells, and how channel activation during pathological tissue acidosis may lead to altered immune cell function that in turn modulates inflammatory pathology in the CNS. We identify gaps in the literature where ASICs and immune cell function has not been characterized, such as neurotrauma. Knowledge of the contribution of ASICs to immune cell function in neuropathology will be critical for determining whether the therapeutic benefits of ASIC inhibition might be due in part to an effect on immune cells.